2013
DOI: 10.1002/2013jd020026
|View full text |Cite
|
Sign up to set email alerts
|

M‐component currents of first return strokes in natural negative cloud‐to‐ground lightning

Abstract: [1] Records of M-component currents of first return strokes in natural negative cloud-to-ground lightning measured in a short instrumented tower are shown along with correlated video records, electric field changes, and relative luminosity. The synchronized fast-camera records clearly match the increase of luminosity of the faint lightning channel. The parameters of these M components are all consistent with those of triggered lightning. According to records of electric field change of lightning events near Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 18 publications
3
14
0
Order By: Relevance
“…In addition to M-components, Malan and Collens (1937) reported on "later components of branched strokes," which followed the return stroke and produced luminosity enhancements in the section of the grounded channel below the observable branching point. Since first stroke channels usually exhibit branches created by the stepped leader, some of the early M-components observed by Visacro et al (2013) are probably of the same nature as the branch components reported by Malan and Collens (1937).…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…In addition to M-components, Malan and Collens (1937) reported on "later components of branched strokes," which followed the return stroke and produced luminosity enhancements in the section of the grounded channel below the observable branching point. Since first stroke channels usually exhibit branches created by the stepped leader, some of the early M-components observed by Visacro et al (2013) are probably of the same nature as the branch components reported by Malan and Collens (1937).…”
Section: Introductionsupporting
confidence: 65%
“…For “early” M‐components, which immediately followed the first‐return stroke current peak, they reported a factor of 3 larger charge transfer to ground than that observed for M‐components in rocket‐triggered lightning by Thottappillil et al (). It is possible that M‐components reported by Visacro et al () were superimposed on the tail of return stroke current (as opposed to being superimposed on CC), which is expected to last up to 3 ms or so. In addition to M‐components, Malan and Collens () reported on “later components of branched strokes,” which followed the return stroke and produced luminosity enhancements in the section of the grounded channel below the observable branching point.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…When measured at the channel base, the current pulses associated with the M component mode of charge transfer exhibit a more or less symmetrical waveshape (Fisher et al, 1993;Paul & Heidler, 2018;Thottappillil et al, 1995;Visacro et al, 2013) and they are responsible for the above mentioned transient enhancement in the channel luminosity (Campos et al, 2007;Flache et al, 2008;Jordan et al, 1995;Malan & Schonland, 1947;Qie et al, 2011;Stolzenburg et al, 2015;Winn et al, 2012;Zhou et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…And based on this conclusion, Campos et al [, ] investigated waveshapes of light signal during continuing current (CC) for negative and positive CG lightning from high‐speed video observation. Visacro et al [] showed that the profiles of current and relative light intensity were similar for M‐component of first return strokes. Recently, taking advantage of rocket‐triggered lightning, further works have been carried out on the current/light correlation.…”
Section: Introductionmentioning
confidence: 99%